Social media: The forefront of pediatric surgical education, recruitment, and information - Rodrigo G Gerardo; Ellen M Encisco; Kiersten P Miller; Todd A Ponsky; Arturo Aranda (Journal of Pediatric Surgery Open, 2023)
Background: The use of social media and mobile applications in surgery has grown exponentially over the past decade with a wide array of functions ranging from surgical education, recruitment to training programs, and improving the ability to share clinical information. It behooves surgical training programs and pediatric surgeons to engage in social media as the modern surgical trainee is learning and networking on a professional level through social media platforms on their mobile devices. Methods: This is a retrospective analysis of social media analytics from a single general surgery residency program as well as an online pediatric surgery educational resource, StayCurrentMD. Social media followers were stratified by age groups. Furthermore, we summarize the various uses for social media and mobile applications for surgical trainees and pediatric surgeons. Results: The StayCurrentMD social media followers from Facebook, Instagram, TikTok, and YouTube included 10,218 total followers and the Wright State University General Surgery Residency had 2,066 followers from Facebook and Instagram. The age group for most followers was 25–34 years of age for all social media platforms except for Facebook which had slightly higher proportions of followers in the 35–44 age group. Conclusion: The modern medical student does not learn about training programs from in-person interviews and today's surgical trainee is no longer in the library to read about surgical technique or current practice guidelines – they're on their phones. Surgical training programs, surgical societies, and surgical educators of the world need to adapt to these changes in technology to improve surgical education and distribute information to surgical providers on a potentially global scale.